Impact of Patient Alignment on Image Quality in C-Arm Computed Tomography – Evaluation Using an ACR Phantom - Alikhani, Babak; Renne, Julius; Maschke, Sabine; Hinrichs, Jan B.; Wacker, Frank K.; Werncke, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose To evaluate the influence of patient alignment and thereby heel effect on the image quality (IQ) of C-arm flat-panel detector computed tomography (CACT).Materials and Methods An ACR phantom placed in opposite directions along the z-axis (setup A and B) on the patient support was imaged using CACT. Image acquisition was performed with three different image acquisition protocols. The images were reconstructed with four convolution kernels. IQ was assessed in terms of high contrast using the modulation transfer function (MTF) and low contrast by assessing the image noise, signal-to-noise ratio (SNR) and contrast-to-noise ratios (CNR) as well as the reliability of density measurements. Furthermore, the dose intensity profiles were measured free-in-air.Results The MTF in setup B is higher than the MTF measured in setup A (p < 0.01). The image noises measured in setup A for the air and bone inserts were higher compared to those measured in setup B (p > 0.05). Opposite behavior has been observed for the polyethylene, water-equivalent and acrylic inserts. The SNR for all inserts is inversely related to the image noise. A systematically increasing or decreasing trend of CNR could not be observed (p > 0.05). The intensity profile measured by the detector system free-in-air showed that the anode heel effect is perpendicular to the z-axis.Conclusion The patient alignment has a minor influence on the IQ of CACT. This effect is not based on the X-ray anode heel effect but is caused mainly by the non-symmetrical rotation of CACT.Key Points: Citation Format
Keywords: C-arm flat-panel detector computed tomography; flat-panel detector; patient alignment; heel effect; image quality